The emotional labour of researching hate crime - Zempi, Irene (Disability hate crime, 2025)
This chapter examines the role of emotionality, positionality, and emotional labour when researching hate crime. I draw upon my own experiences of researching hate crimes for more than a decade, especially as an outsider researcher investigating anti-Muslim hate crimes. I present an honest reflection on the challenges and opportunities that we come across as researchers when researching the field of hate studies. In doing so, the reader, or a potential researcher, can draw parallels for any research with disabled victims of hostility. The chapter concludes by assessing the value of embracing emotionality and offers methodological guidance for future researchers.